2004
DOI: 10.1021/ma0348066
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Opening Polymerization of ε-Caprolactone Initiated by Natural Amino Acids

Abstract: Introduction. Poly( -caprolactone) (PCL) is currently being investigated for use in medical devices and pharmaceutical controlled release systems because of its biocompatibility, biodegradability, and good drug penetrability. [1][2][3] PCL is usually synthesized by ringopening polymerization (ROP) of -caprolactone ( -CL), which is carried out in the presence of metal-contained 4-8 or metal-free compounds. [9][10][11][12][13] The ROP can be initiated by active hydrogen of amine and alcohol, [14][15][16] and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 17 publications
3
91
0
Order By: Relevance
“…7 Considerable effort has been directed toward the evaluation of various types of both organic acids/bases for the ROP of cyclic esters, 7-37 cyclic carbonates, [38][39][40][41][42][43] epoxides, [44][45][46][47] lactams, 48 cyclic (carbo)siloxanes, 49 cyclic phosphates, [50][51][52][53][54] etc. Regarding the ROP of cyclic esters, organic Brønsted acids, e.g., methane sulfonic acid (MSA) and triflimide, were found to be suited for the polymerization of lactones, [8][9][10][11][12][13][14][15][16][17][18][19] whereas organic bases, e.g., 1,8-diazadicyclo [5.4.0]undec-7-ene (DBU) and 4-dimethylaminopyridine (DMAP), were effective for the ROP of the lactide (LA). 7,[20][21][22][23][24]26 In addition, the bifunctional catalytic system possessing two activation sites for the monomer and propagating chain end also turned out to be effective for the ROP of ε-caprolactone (ε-CL) and LA.…”
Section: Introductionmentioning
confidence: 99%
“…7 Considerable effort has been directed toward the evaluation of various types of both organic acids/bases for the ROP of cyclic esters, 7-37 cyclic carbonates, [38][39][40][41][42][43] epoxides, [44][45][46][47] lactams, 48 cyclic (carbo)siloxanes, 49 cyclic phosphates, [50][51][52][53][54] etc. Regarding the ROP of cyclic esters, organic Brønsted acids, e.g., methane sulfonic acid (MSA) and triflimide, were found to be suited for the polymerization of lactones, [8][9][10][11][12][13][14][15][16][17][18][19] whereas organic bases, e.g., 1,8-diazadicyclo [5.4.0]undec-7-ene (DBU) and 4-dimethylaminopyridine (DMAP), were effective for the ROP of the lactide (LA). 7,[20][21][22][23][24]26 In addition, the bifunctional catalytic system possessing two activation sites for the monomer and propagating chain end also turned out to be effective for the ROP of ε-caprolactone (ε-CL) and LA.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Metal complexes are the most commonly explored catalysts for the production of polycaprolactone. Previous examples of metal complexes used as catalysts include tin, 2,6,[15][16][17][18][19][20][21] aluminum, 6,10,18,19,[22][23][24][25][26][27] iron, 6,18 scandium, 1,12,28 yttrium, 14,18,[29][30][31][32][33][34][35] zinc, [36][37][38][39] and other metals.…”
Section: Introductionmentioning
confidence: 99%
“…11 These reactions show characteristics of a controlled, living reaction (e.g., conversion shows a linear relationship to reaction time, molecular weight shows a linear dependence on conversion, and the resulting polymers show a low polydispersity). 3,11,46 Other purely organic systems that display catalytic activity include natural amino acids, 9 organic acids, 47 and acid/alcohol systems. 13 Unfortunately, these catalysts are all homogeneous species 48 that, while not contaminating the polymer with metal residue, are not easily recoverable from the reaction mixture, making catalyst recovery and recycle problematic.…”
Section: Introductionmentioning
confidence: 99%
“…The studies performed by Liu and coworkers showed that they are also effective as initiators of ROP of CL (Liu & Liu, 2004). Authors found hat the number-average molecular weights of the obtained polymers did not exceed 5700 Da and that used amino acids were incorporated into macromolecule chain ( Figure 6).…”
Section: Natural Initiators and Organocatalysts Of Ring-opening Polymmentioning
confidence: 99%